Water mass mixing contributes dynamics of dissolved organic matter in Kuroshio-Oyashio confluence region - Wang, Yasong; Liu, Bilin; Wu, Weichao; Liu, Liang; Wang, Yinghui; Xu, Yunping (Frontiers in Marine Science, 2023)
The Kuroshio-Oyashio confluence region (K/O region) plays a significant role in the global carbon cycle and climate change. In this study, we examined the concentration and composition of dissolved organic matter (DOM) in water samples collected from depths of 0 to 1000 meters between 2019 and 2021. The concentration of dissolved organic carbon (DOC) ranged from 30.54 to 113.21 μmol L-1, with higher concentrations observed in surface waters. The biological index (BIX) decreases with increasing depth, indicating decreasing in-situ production of plankton downwards. Additionally, the humification index (HIX) increased with depth, suggesting the transformation of labile to refractory DOC by bacteria. Using parallel factor analysis, we identified two humic-like (C1, C3) and one protein-like (C2) fluorescent components in 467 water samples. Water samples collected in 2020 exhibited significantly higher specific ultraviolet absorbance at 254 nm (SUVA254) (0.5 ± 0.2 L mg-1 m-1) and higher intensities of C1 (8.2 ± 2.69 *10-3 R.U.) and C3 (9.22±4.39 *10-3 R.U.) compared to samples from 2019 and 2021. We found that water temperature had a positive correlation with C2 intensity (r = 0.33; p < 0.01), but negative correlations with C1 (r = −0.72; p < 0.01) and C3 intensity (r = −0.55; p < 0.01). Comparison of measured and theoretical values using a conservative physical mixing model revealed active biogeochemical processes of DOM during water mixing of the Kuroshio, Oyashio, and North Pacific Intermediate Water that change concentration and composition of DOM. Since the hydrology in the K/O region is sensitive for the ongoing climate warming, further investigation is needed to understand water mass mixing and associated DOM dynamics.